Strengthening The Character Trait of Peacefulness through Habitual Communication Practice of ‘3S’ (Smiling, Greeting, Saying Hello) at Early Childhood Education and Care - Haq, Muhammad Dhiyaul; Muslimin, Khoirul; Subaidi, Subaidi; Kalupae, Abdulaziz (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
Abstract: This study aims to describe the reinforcement of the character trait of peacefulness in students through the habitual communication practice of the